Magnetoelectric Hysteresis of Bi-Layered Magnetoelectric Composite. Issue 2 (3rd April 2018) - Zhou, Yun; Wang, Su-Su; Gao, Tian-Xiang; Wang, Jian-Feng; Chen, Miao-Gen; Jiao, Zhi-Wei; Wu, Liang
Abstract : Magnetoelectric hysteresis behavior for a bi-layered magnetoelectric composite has been investigated. The results show that the magnetoelectric voltage coefficients are deeply affected by the bias magnetic field and test period. The observed coercive field, remanence, and ratio of remanence of the magnetoelectric hysteresis loops with the test period obey an exponential decay law. In addition, the bias magnetic field dependence of magnetoelectric hysteresis loops is found to be associated with magnetic hysteresis loops. These findings provide some ideas not only for practical applications, but also for the magnetoelectric effect examinations of magnetoelectric composites.